A Review on Human Resource Management Based on Local Wisdom - ZUHRI, Saifudin; HERAWAN, Tutut; WENING, Nur; HARSONO, Mugi (Journal of Advanced Research in Law and Economics, 2019)
The critical discourse in management studies has begun to emerge and received serious attention from experts with different scientific backgrounds. Human resource management (HRM) as one of the focuses in management studies has now been reviewed from a variety of critical perspectives which involve multidisciplinary approaches. This article aims to review previous works on social capital and local wisdom in various fields of study, which are then analyzed more specifically from the perspective of HRM. In order to bring local wisdom as a new discourse in HRM, this article presents a depth review on related articles that are relevant to the topic. The articles collected from various sources were critically identified in terms of the methods/models, benefits, and limitations. After the collection and identification, mapping of the review results was conducted to find a gap which would serve as an opportunity for researchers who are concerned with critical management studies, especially related to the use of social capital sourced from local wisdom in the maintenance of human resources. Local wisdom-based HRM is the revitalization of local and traditional values that are commonly found in various regions in Indonesia that could be the beginning or inspiration for researchers to explore social capital in corporate contexts in the future. This article also provides new insights to be developed by HRM researchers in the future, that local wisdom can be an alternative in human resource management in line with the strengthening of critical management study.